Teaching accounting for the fourth industrial revolution: ICT integration in South African schools - Siyaya, Mlindeni Celinhlalo; Ajani, Oluwatoyin Ayodele (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
This study examines the integration of Information and Communication Technology (ICT) in the teaching of accounting in South African secondary schools, focusing on the ILembe District. In the context of the Fourth Industrial Revolution, ICT use is increasingly essential for enhancing pedagogical practices and developing learners’ digital competence. Using a qualitative design, semi-structured interviews were conducted with ten accounting teachers, and the data were analysed thematically. The findings show that although teachers recognise ICT’s value for improving learner engagement and understanding, its effective use is constrained by inadequate infrastructure, limited access to devices, insufficient professional development, and resistance to technological change. Teacher motivation, departmental support, and learner interest were identified as key enablers. To address the uneven integration of ICT across schools, the study recommends targeted and sustained professional development as a central intervention. In response to the identified needs, the study proposes an ICT-Driven Teachers’ Professional Development Model (ICT DTPM) to guide future capacity-building efforts. The findings contribute to ongoing discussions on ICT in education and offer practical insights for strengthening accounting education in line with the demands of the Fourth Industrial Revolution.